Keteladanan Guru dalam Pelaksanaan Salat Berjamaah untuk Peningkatan Kedisiplinan Siswa Di MTS Al-Maarif Panyiwi Kec. Cenrana Kab. Bone - Sayang, Sayang (Institut Agama Islam Negeri (IAIN) Bone, 2020)
This thesis discusses about “Exemplary Teacher In Conducting Congregational Prayers To Improve The Discipline Of Middle School Students At Al-Ma’arif Panyiwi Cenrana Sub District Bone District”. The primary objects in this study are students and other elements within the school environment, with data collection techniques in the field research, including observation, interview and documentation techniques. The approach used is a psychological approach, pedagogical and sociological approach. The results showed that the managerial existence of student coaching in the implementation of prayer in congregation in the mosque with all its programs has a significant contribution in shaping the good character or noble character of Madrasah students, including discipline. There are several forms of managerial methods or steps implemented by the teacher in carrying out student coaching programs to carry out the congregation prayer, namely the method of giving examples or role models to students with discipline in teaching and participating in the congregation prayer together with students (students be a figure), supervision (controlling) by involving students. The method of controlling is carried out through recording the names of the students who violated and giving sanctions in the form of memorizing verses of the Qur'an. Factors that support the implementation of the midnight congregational prayer program are the participation and enthusiasm of students in carrying out congregational prayers, the existence of facilities in the form of mosques and support from the school. The inhibiting factors, namely facilities or places of ablution are still limited. The impact of applying congregational prayer for students of Middle School at Al-Ma’arif namely the impact on affective and religious on students such as the intensity of worship and shape student discipline. The implication of this research is all elements of the school, especially to teachers to understand again how important the existence of an example in carrying out programs that are incidental and primary both the learning process and school activities, especially in terms of the implementation of congregational prayers, and continue to innovate- Innovative and up to date innovation in carrying out the mandate as a figure that is expected to be able to advance the world of education.